Comparative study of the substantia nigra echogenicity and 123I-Ioflupane SPECT in patients with synucleinopathies with and without REM sleep behavior disorder - Mašková, J; Školoudík, D; Štofaniková, P; Ibarburu, V; Kemlink, D; Zogala, D; Trnka, J; Krupička, R; Šonka, K; Růžička, E; Dušek, P (Sleep medicine, 2020)
OBJECTIVES: Hyperechogenicity of the substantia nigra (SN) and abnormal dopamine transporter-single-photon emission computed tomography (DAT-SPECT) are biomarkers commonly used in the assessment of prodromal synucleinopathy. Our goals were as follows: (1) to compare echogenicity of SN in idiopathic rapid eye movement (REM) behavior disorder (iRBD), Parkinson's disease (PD) without RBD (PD-noRBD), PD with RBD (PD + RBD), and control subjects; and (2) to examine association between SN degeneration assessed by DAT-SPECT and SN echogenicity. PATIENTS/METHODS: A total of 61 subjects with confirmed iRBD were examined using Movement Disorders Society-unified PD rating scale (MDS-UPDRS), TCS (transcranial sonography) and DAT-SPECT. The results were compared with 44 patients with PD (25% PD + RBD) and with 120 age-matched healthy subjects. RESULTS AND CONCLUSION: The abnormal SN area was found in 75.5% PD, 23% iRBD and 7.3% controls. Median SN echogenicity area in PD (0.27 ± 0.22 cm2) was higher compared to iRBD (0.07 ± 0.07 cm2; p < 0.0001) and controls (0.05 ± 0.03 cm2; p < 0.0001). SN echogenicity in PD + RBD was not significantly different from PD-noRBD (0.30 vs. 0.22, p = 0.15). Abnormal DAT-SPECT was found in 16 iRBD (25.4%) and 44 PD subjects (100%). No correlation between the larger SN area and corresponding putaminal binding index was found in iRBD (r = -0.13, p = 0.29), nor in PD (r = -0.19, p = 0.22). The results of our study showed that: (1) SN echogenicity area in iRBD was higher compared to controls, but the hyperechogenicity was present only in a minority of iRBD patients; (2) SN echogenicity and DAT-SPECT binding index did not correlate in either group; and (3) SN echogenicity does not differ between PD with/without RBD.
Keywords: Synucleinopathies; Neuroimaging; Parkinson's disease; Substantia Nigra; Tomography, Emission-Computed, Single-Photon; Idiopathic rapid-eye-movement sleep behavior disorder; substantia nigra; radioizotopy jodu; Nortropanes; Dopamine transporter imaging; Transcranial sonography; synukleinopatie; Humans; Substantia nigra hyperechogenicity; ultrasonografie dopplerovská transkraniální; REM Sleep Behavior Disorder; Ultrasonography, Doppler, Transcranial; nortropany; jednofotonová emisní výpočetní tomografie; porucha chování v REM spánku; Iodine Radioisotopes; lidé